An analysis of the predominant causes of deterioration of concrete structures in South Africa - Mashanda, Darison (Department of Civil Engineering, 2019)
Concrete deteriorates due to, but not limited to the ingress of deleterious substances which react with the cement matrix, reinforcing bars corrosion, mechanical effects, physical effects, structural damages, poor construction practices. All these factors individually or combined, ultimately reduce the expected service lives of the concrete structures. The trends vary with different exposure conditions and geographical locations, and a reference guide is required in South African context. A total of twenty-four concrete structures were visually assessed by different University of Cape Town (UCT) scholars and findings were captured in project reports. The reports of these assessments were analysed in this research to identify the main causes of concrete deterioration and severity of damages in the three provinces considered in South Africa, whilst linking these to environmental exposure conditions and geographical location. It is important to elucidate that deterioration mechanisms and trends were drawn from the limited number of visual assessment reports, and the mechanisms assumed might not have been necessarily correct. The rating of the defects was done using the DER-U rating system, a method available for bridges and retaining walls. DER-U rating system was developed for buildings, exploiting the available rating system for bridges as there is no available established rating system for buildings, and the author considered it an important tool for the preliminary evaluation taking note of all limitations. However, reinforcing bars corrosion has been found to be the most prominent deterioration mechanism on structures assessed and severity was high on the structures located in the Western and Eastern Cape provinces, and was exacerbated by the inadequate cover provided on most structures. Furthermore, it was also noted that the severity of the damage increased with age of a structure. Although petrographic analysis as an additional investigation was required to ascertain Alkali-Silica Reaction (ASR), damage was observed in the Western Cape and Gauteng provinces. Even though the occurrence was low, it still required special attention as the effects are usually disastrous and very expensive to maintain the affected structures. Leaching was observed on all the bridge structures assessed though it was more prominent on the structures situated at the coast. Plastic and drying shrinkage cracks were observed on all structures in the Gauteng province and it has been noted from the literature that shrinkage cracks were exacerbated by very high seasonal temperatures in these provinces. Abrasion was high on all structures on the tidal zones and the elements of structures located in the water courses. The proposed in-situ and laboratory tests have been discussed in this report and they are recommended for full-scale condition assessments to complement the visual assessments in an endeavour to ascertain the mechanisms identified. Evidence of poor maintenance practices was observed in the Eastern Cape province where delamination and spalling were observed on freshly repainted structures. As a result, in South Africa there is undoubtedly, a constant need of developing and employing effective and efficient tools to ensure quality is not compromised. Design engineers must always take into cognisance the exposure conditions and ensure strict quality control measures during the construction phase. Maintenance engineers should take into consideration the location of the structure and deterioration mechanisms in the specific areas when determining the maintenance strategies. The clients should always employ knowledgeable design and maintenance engineers, to ensure durable structures are erected and correctly maintained.